INNOVATION CULTURE AMONG ACADEMICIANS IN BIOTECHNOLOGY R&D IN MALAYSIAN RESEARCH UNIVERSITY - Othman, Siti Norezam; Yaacob, Noorulsadiqin Azbiya; Yamin, Fadhilah Mat; Ismail, Risyawati Mohd (Journal of Technology Management and Business, 2014)
How to get universities to better contribute to the innovation process has become an important issue in the evolution of the roles of institutions of higher education. This study sought to identify perceptions of academic researchers involved in biotechnology related research with regard to their commercialization activities of their researches by using a survey questionnaire. Based on the survey data, factor analysis was conducted to group commercialization activities variables into descriptive components. Subsequently, Kruskal Wallis tests were further carried out to differentiate the commercialization activities based on the demographic background. From the survey, it is apparent that most academic researchers perceived their commercialization activities are geared towards publication activities. Based on the factor analysis, commercialization activities of biotechnology related researches were found to consist of three groups; committee and network building (CNB), technology transfer (TT) and intellectual property and academic writing (IPAW). Findings of Kruskal Wallis tests showed that demographic background affects academic researchers who were involved in commercialization activities of biotechnology related researches.